2022
DOI: 10.1021/acs.jafc.1c07568
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Alleviates Dextran Sulfate Sodium-Induced Colitis by Modulating Inflammatory Responses, Intestinal Barrier, and Microbiome

Abstract: Hydroxytyrosol (HT), a polyphenol derived from olive oil, was examined against dextran sulfate sodium (DSS)-induced colitis to study its potential in preventing colitis and the underlying mechanisms involved. The low dose and high dose of HT used in mice were 10 and 50 mg/kg, respectively. Research findings have shown that HT is effective in preventing colitis by alleviating the signs of colitis. HT intervention significantly reduces colitis markers such as myeloperoxidase (MPO) and proinflammatory cytokine (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…40,41 In addition, we also found that the taxa of Turicibacter and Colidextribacter were significantly elevated by fucoidan treatment, which were also classified as beneficial bacteria that promoted the production of SCFAs. 42,43 Additionally, Parasutterella can produce succinate to support the cross-feeding of gut microbiota. 44 Several studies indicated that this taxon plays an active role in bile acid metabolism, especially secondary bile acid biosynthesis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…40,41 In addition, we also found that the taxa of Turicibacter and Colidextribacter were significantly elevated by fucoidan treatment, which were also classified as beneficial bacteria that promoted the production of SCFAs. 42,43 Additionally, Parasutterella can produce succinate to support the cross-feeding of gut microbiota. 44 Several studies indicated that this taxon plays an active role in bile acid metabolism, especially secondary bile acid biosynthesis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Inflammation is a major feature of colitis, and the proinflammatory cytokines (TNF-α, IL-1β, and IL-6) are involved in the development and pathogenesis of UC [ 79 ]. The increased secretion of proinflammatory cytokines causes colon damage during colitis [ 80 ]. Therefore, inhibiting these proinflammatory cytokines could mitigate UC in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an increased ratio of Firmicutes to Bacteroidetes markedly affects energy gain in dairy cows [ 50 ]. Lachnospiraceae , Ruminococcaceae , and Colidextribacter are mainly SCFAs producing bacteria [ 29 , 30 , 51 , 52 ]. Here, higher abundances of Firmicutes to Bacteroidetes was found, Romboutsia (phylum Firmicutes ), CHKCI001 (family Lachnospiraceae ), Faecalibacterium (family Ruminococcaceae ), Colidextribacter and lower abundances of Bacteroidetes in the cecal contents of geese in the CCHMA group than in those of in CON group.…”
Section: Discussionmentioning
confidence: 99%